IMPROVEMENT OF COMMERCIAL BANKS' CAPITAL AND ITS ECONOMIC EVALUATION METHODS - ERGASHEV, AXMADJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
It consists in the development of a scientific proposal and practical recommendations aimed at improving the effective management and evaluation mechanisms of the capital of commercial banks. This article examines the capital of commercial banks and its economic evaluation methods, as well as factors affecting the capital of banks, the financial performance of commercial banks. criteria and indicators for assessing stability are presented.